Pengelolaan sinyal digital dan sistem pemrosesan sinyal Teori dan penyelesaian / Harlianto Tanujaya ; editor, Agnes Heni T - TANUJAYA, Harlianto; Heni T, Agnes (Andi, 2007)
viii, 218 [4] hlm. ilus. 21 cm.